2015
DOI: 10.1002/adem.201500410
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Performance Monitoring of Three‐Way Catalytic Converters by Self‐Regenerative and Adaptive High‐Temperature Catalyst and Sensors

Abstract: This study reports the performance of a self‐regenerating perovskite, LaFeCoPdO3 as a three‐way catalyst (TWC) and its use for self‐diagnostic by means of integrated Al‐doped TiO2 and LaFeCoPdO3 sensor arrays, consisted of semiconducting oxides as sensing layers and LaFeCoPdO3 as catalytic filter. Although perovskite catalyst yields a reasonable NO conversion performance at lower temperatures, it cannot fully compete with a commercial TWC under the TWC relevant temperatures and conditions. On the other hand, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This allows the catalyst be highly responsive to the frequent P O 2 swings of the ICE exhaust . It was also suggested that the facile segregation and reincorporation of the Pd species can inhibit the sintering of metallic Pd particles. ,,, The reductive segregation of Pd 0 on the surface layer of the catalysts can occur at low temperatures (∼100 °C or higher). Meanwhile, oxidation of Pd 0 to Pd 2+ and its (partial) reincorporation into the perovskite framework occurs at ∼200 °C in an oxidative atmosphere .…”
Section: Perovskites As Oxygen Storage Materials In Three-way Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…This allows the catalyst be highly responsive to the frequent P O 2 swings of the ICE exhaust . It was also suggested that the facile segregation and reincorporation of the Pd species can inhibit the sintering of metallic Pd particles. ,,, The reductive segregation of Pd 0 on the surface layer of the catalysts can occur at low temperatures (∼100 °C or higher). Meanwhile, oxidation of Pd 0 to Pd 2+ and its (partial) reincorporation into the perovskite framework occurs at ∼200 °C in an oxidative atmosphere .…”
Section: Perovskites As Oxygen Storage Materials In Three-way Catalysismentioning
confidence: 99%
“…For instance, the complexity for some of the doped perovskites makes the preparation of structured OSMs in commercial TWC systems challenging: wash-coated monolithic perovskite catalysts that usually contain complex components to obtain stable structure, perovskite oxides may react with the substrate, binder, or primer materials, resulting decreased catalytic activity and/or OSC. ,,, Other challenges include stability issues in the presence of sulfur for some perovskites. Self-regeneration of PGM can also be limited under certain practical exhaust conditions; over-reduction can lower NO reduction activity, and overoxidation of the materials can permanently lower activity for CO and HC oxidation reactions via the sintering of perovskite particles. The complexity of advanced perovskite system is also an issue.…”
Section: Perovskites As Oxygen Storage Materials In Three-way Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…This Rh-incorporating perovskite has a self-regenerative property which results in the segregation of Rh nanoparticles on the reduction and re-incorporation into the lattice upon oxidation [25]. Relying on the NO oxidizing capability of Rh, the effects caused on a sensor due to the high-temperature deviations in NO2 containing gas environments can be eliminated.…”
Section: Al-doped Tio2 Sensor Layermentioning
confidence: 99%
“…Tanaka et al investigated regeneration ability of a perovskite, which responded in accordance with environmental input [13,14]. This enables the perovskite framework to accommodate metals that can also migrate from one site to another [4,[15][16][17][18]. For example, the status of Pd inside the lattices of a perovskite changes reversibly between oxidation and reduction atmospheres, which benefits its long-term catalytic performance for exhaust treatment [10].…”
Section: Introductionmentioning
confidence: 99%